2010
DOI: 10.1373/clinchem.2009.129742
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Increased Body Mass Index on Accuracy of B-Type Natriuretic Peptide (BNP) and N-Terminal proBNP for Diagnosis of Decompensated Heart Failure and Prediction of All-Cause Mortality

Abstract: Background: BNP and N-terminal proBNP (NT-proBNP) concentrations may be depressed in patients with increased body mass index (BMI). Whether increased BMI affects accuracy of these biomarkers for diagnosing decompensated heart failure (HF) and predicting outcomes is unknown. Methods: We measured BNP and NT-proBNP in 685 patients with possible decompensated HF in a free-living community population subdivided by BMI as obese, overweight, and normal weight. HF diagnosis was adjudicated by a cardiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 30 publications
(38 reference statements)
1
31
0
Order By: Relevance
“…This makes levels of natriuretic peptide less helpful in the diagnosis of HF in obese patients, because patients can have normal or minimally elevated levels of BNP, even in the setting of acute decompensated HF and elevated filling pressures. 359,360 Because signs and symptoms of dyspnea and edema are not specific for HF in obese patients, and jugular venous pressure can be difficult to estimate accurately because of body habitus, hemodynamic confirmation may be needed more often in obese than in lean patients to confirm the clinical diagnosis of HF.…”
mentioning
confidence: 99%
“…This makes levels of natriuretic peptide less helpful in the diagnosis of HF in obese patients, because patients can have normal or minimally elevated levels of BNP, even in the setting of acute decompensated HF and elevated filling pressures. 359,360 Because signs and symptoms of dyspnea and edema are not specific for HF in obese patients, and jugular venous pressure can be difficult to estimate accurately because of body habitus, hemodynamic confirmation may be needed more often in obese than in lean patients to confirm the clinical diagnosis of HF.…”
mentioning
confidence: 99%
“…Based on the established clinical threshold of 100 pg/mL, BNP testing yielded false negative results in 20% of obese HF patients [6,116]. Hence, a cut point of BNP ≤ 54 pg/mL is recommended for ruling out CHF in severely obese patients (BMI ≥ 35) (Table 1) [6].…”
Section: Validity Of Bnp As a Marker For Chf In Obese Patientsmentioning
confidence: 99%
“…Some studies were based on large population [4,5,62,63,106], including both healthy adult subjects and patients with various disorders (only patients with HF were excluded), while other studies included only patients with HF [8][9][10][11]105] (Table 2). However, conflicting results were also reported; Kanda et al [113] found no significant correlation between BNP to BMI values in a general Japanese population, including 686 apparently healthy subjects.…”
Section: Role Of Sex Steroid Hormonesmentioning
confidence: 99%
“…This phenomenon, termed ''reverse epidemiology'' and involving about 20 million Americans, may be due to the overwhelming effect of the malnutrition-inflammation complex syndrome (MICS) [131]. The presence of MICS in some patients contributes to explain the inverse correlation between BMI and BNP values in HF [6,[8][9][10][11]105]. BNP production/secretion is greatly increased in elderly HF patients with severe disease, hemodynamic impairment, and activation of counteracting neurohormone (including adrenergic, renin-angiotensin-aldosterone, and endothelin) and cytokine systems compared to asymptomatic subjects [13,[30][31][32][33][34][35].…”
Section: Role Of Possible Confounding Variables: Difference In Analytmentioning
confidence: 99%